2008
DOI: 10.1093/ndt/gfn588
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous plasma carnitine pool composition and response to erythropoietin treatment in chronic haemodialysis patients

Abstract: These data illustrate the relationship between carnitine levels and response to rHuEPO treatment in haemodialysis patients, in particular, the importance of the proportion of long-chain acylcarnitines within the plasma carnitine pool. This proportion may be more indicative of the response to L-carnitine supplementation than absolute L-carnitine levels alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 40 publications
2
34
1
Order By: Relevance
“…There are some studies that found a significant negative correlation of plasma total carnitine levels and rHuEPO requirement in hemodialyzed patients [19,20]. In our study, there was no significant difference in the plasma carnitine levels before or after treatment between responders and nonresponders.…”
Section: Discussioncontrasting
confidence: 53%
“…There are some studies that found a significant negative correlation of plasma total carnitine levels and rHuEPO requirement in hemodialyzed patients [19,20]. In our study, there was no significant difference in the plasma carnitine levels before or after treatment between responders and nonresponders.…”
Section: Discussioncontrasting
confidence: 53%
“…They cannot be extended to long-term dialysis patients with more profound carnitine deficiency (2,28). These carnitine-deficient patients have a higher risk for hyporesponsive rHuEPO-dependent anemia (28). Further studies must clarify whether these patients require carnitine supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…(f) Angiotensin converting enzyme inhibitor (ACEI) class of drugs are also related to EPO resistance, as first reported by Reuter et al [38]. A study involving dialysis patients.…”
Section: Erythropoietin Resistancementioning
confidence: 91%